RANCANG BANGUN SIMULATOR KAPAL MOTOR MENGGUNAKAN PANEL SURYA - Tharo, Zuraidah; Anisah, Siti; Hamdani, Hamdani; Ginting, Justra; Kusuma, Budhi Santri (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
Solar power generation is one of the many renewable energies whose use has begun to develop until recently. In this case the use of solar panels is intended for boat / fishing boat simulators, which aim to provide technological innovation and use of natural resources as a substitute for petroleum fuels. Using solar panels, batteries, solar charge controllers and dc motors, a boat / fishing boat simulator is made that can operate during the day for about 2 hours, with a battery voltage of 5.11 volts and a current of 176 mA and at night it can only operate for about 15-20 minutes. with voltages below 3 volts and currents below 100 mA. To further maximize the system, we recommend using a solar panel and a larger battery